THE WESTERN MEDITERRANEAN SEISMOLOGICAL NETWORK - Pazos, A. (2006)
The Royal Naval Observatory in San Fernando (ROA), together with the Complutense University from Madrid (UCM), and in collaboration with the GeoForschungsZentrum of Potsdam (GFZ), have deployed a broad band seismic network around the Alboran sea, in southern Spain, northern Africa. This network started to operate in 1996 with the installation of the SFUC station, near the Observatory. Since then, several stations have been installed and nowadays it is being in expansion with the future installation of several ocean bottom seismometers (OBS). This network is called the Western Mediterranean Network (WM). In this work the present status and the future of the broad band WM network are shown.